Experimental evaluation of surface finish in cylindrical grinding of Al7075/RHA/BN composite. (2021) - Paranthaman, P.
Abstract: The present study is focused on the fabrication and machinability analysis of economical composite material with agro waste reinforcements. The base material is Aluminium 7075 whereas the rice husk ash (RHA) is preferred as reinforcement to fabricate this innovative composite through squeeze casting. A minimal amount of (2%) BN is also added to improve the surface roughness. The weight percentage of RHA is varied from 5 to 15% with steady rise of 5%. The fabricated composite is analyzed for its machinability in cylindrical grinding process with surface roughness (Ra) as an objective function. The input parameters taken into considerations are RHA%, table feed and depth of cut. The results indicated that the surface roughness of the composite is heavily influenced by the reinforced RHA wherein table feed and depth of cut has negative effect over the surface finish.